Por uma poética do eco em Marília Garcia - Carina Santos Gonçalves (2021)
The purpose of this thesis is to investigate how the echo appears in Marília Garcia’s poetics. After analysing the types of quotations used by the poet, I delve deeper into the method of self- citation, thus relating it to repetition and its effects (such as performance and simultaneity) on the author's poems. Then, I observe the rhythm in Garcia's poetic compositions. Taking the essay form as the guide of this investigation, I rely on Octavio Paz’s thinking and, especially, on the concept of ritornello, created by Gilles Deleuze and Félix Guattari. In the third chapter, I verify how Garcia investigates emotions and feelings through the idea of echo. Finally, I associate echo, performativity, images and maps based on my readings of authors such as Hans Gumbrecht and Walter Benjamin.